The images of God in religious discourses on race, gender and sexuality in contemporary Africa: A theology of Ubuntu - Shingange, Themba (Verbum et ecclesia, 2025)
The depictions of the mental images of God in religious discourses on race, gender and sexuality are global phenomena, which are often marked by controversy. In Africa, Christianity has, since its inception, presented a particular narrative about God’s image that bolsters exclusivist perceptions defining who has and who has no place in the household of God. Thus, these narratives inadvertently contributed to the creation of unsafe spaces for certain categories of people in society because of their race, gender and sexuality. This article looks at the historical presentation of God’s image by the 19th-century missionaries in Africa. Conversely, it analyses how such a presentation contradicted the African images of a Supreme Being and how it further contributed to the creation and perpetuation of unsafe spaces for black people, women, and LGBTQ+ people in contemporary African church and society. Then, it discusses how the African concepts of race, gender and sexuality challenge the norm and call for a transformed presentation of the images of God that resonates with the theology of Ubuntu, the divine revelation, and their manifestations in the images of God that are freeing. Intradisciplinary and/or interdisciplinary implications: The study has interdisciplinary implications as it engages theology and missiology with the intersectionality and interdisciplinary discourses of race, gender, sexuality studies and the African philosophy of Ubuntu. This is critical in ensuring the prophetic voice of Christianity, which does not shy away from addressing contemporary societal issues.